DINAMIKA DAKWAH ISLAM DALAM PERSPEKTIF MANAGEMEN PERUBAHAN DI KECAMATAN TAMPAN - Ginda Ginda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Although there are indications of religious and social piety of society lately, which is characterized by increasing volumes of awareness in worship and activities of spiritual routines at almost all levels of society, it is not at the same time expressed to reflect the level of qualitative understanding and practice of Islam. Because there are also indications that suggest that such behaviors are only a symbol of social piety, while worship carried out by the ummah is only limited to carrying out duties and rituals. Majelis Taklim as an Islamic da'wah institution that is continuously present in the community such as not having a contribution in assisting the community